2008
DOI: 10.1007/s12328-008-0042-z
|View full text |Cite
|
Sign up to set email alerts
|

Bronchogenic cyst of the stomach involved with gastric adenocarcinoma

Abstract: Bronchogenic cyst, a congenital anomaly mostly found in the mediastinum, rarely arises in the stomach. A 43-year-old man had epigastric pain and was diagnosed as having gastric adenocarcinoma. Abdominal ultrasonography showed hepatic cyst, and computed tomography and magnetic resonance imaging revealed a cystic lesion near the stomach. At surgery, the cystic lesion was found to be located at the lesser curvature of the stomach where the cancer invasion was seen. Total gastrectomy with combined resection of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Malignant change of GDC lined by PCCE is rare. Shibahara et al (2009) reported a case of bronchogenic cyst of the stomach located at the opposite side wall to the gastric adenocarcinoma, and attributed the adenocarcinoma to the chronic inflammation from the bronchogenic cyst to the gastric mucosa. Worth mentioning, because of persistent exposure to carcinogenic substances, alimentary duplication cyst should be recognized as a lesion at risk for malignant transformation in patients aged more than 50 years (Fukumoto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant change of GDC lined by PCCE is rare. Shibahara et al (2009) reported a case of bronchogenic cyst of the stomach located at the opposite side wall to the gastric adenocarcinoma, and attributed the adenocarcinoma to the chronic inflammation from the bronchogenic cyst to the gastric mucosa. Worth mentioning, because of persistent exposure to carcinogenic substances, alimentary duplication cyst should be recognized as a lesion at risk for malignant transformation in patients aged more than 50 years (Fukumoto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…If this is not possible, segmental gastrectomy is an alternative (Holcomb et al, 1989). When malignant change is seen in the cyst, a surgical procedure without rupture of the cyst is required (Shibahara et al, 2009). Management of asymptomatic cases remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should be vigilant for these complications as they may further complicate surgical intervention due to the associated adhesion ( 32 ). In the 35 cases analyzed in the present study, 3 cases were preoperatively diagnosed by needle biopsy, whereas the majority of the remaining cases were misdiagnosed as stromal tumors or other benign lesions and one previous case was misdiagnosed due to concomitant gastric carcinoma ( 23 ).…”
Section: Discussionmentioning
confidence: 85%
“…Postoperatively, the elevated CA 19–9 levels were found to be normalized. Certain cases also presented with gastric carcinoma ( 23 , 24 ); chronic inflammation of the gastric mucosa resulting from the bronchogenic cyst may have caused adenocarcinoma in the stomach ( 23 ). The present study demonstrated that gastroscopy and imaging examinations may be able to locate the lesion; however, they cannot provide qualitative diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the report of gastric cancer arising in gastric duplication [2,21-23], surgery is nowadays considered the standard treatment for these lesions [24]. The possibility of a malignant transformation is related to the presence of a gastric-type lining epithelium.…”
Section: Discussionmentioning
confidence: 99%